Optical Coherence Tomography (OCT) as a Retinal Biomarker for Brain Neurodegeneration: A Narrative Review - Król, Agata; Muraszewska , Emilia; Muraszewski , Łukasz; Kwitowska, Patrycja; Ubysz, Eryk; Lewandowska, Edyta; Łuczyński, Cezary; Paczkowski , Maciej; Wręczycki , Mariusz; Pyjecka , Małgorzata (Quality in Sport, 2026)
Background. Optical coherence tomography is a rapidly developing imaging technique being increasingly used for the diagnosis of neurodegenerative diseases. It has brought forth new innovations for these diseases. Measurements of the retinal layers, macular and separate layer thicknesses, ganglion cell complex and choroidal thickness etc, have proven to be an excellent indication in differentiating these diseases using non-invasive and minimally invasive procedures. Aim. To summarize available information and studies about the usage of OCT in neurodegenerative diseases which might create a new path for their diagnosis and treatment. Materials and Methods. A literary search was done using the PubMed database to identify relevant studies published in English within the last 10 years. The selected studies were analysed to summarize current evidence regarding the potential role of OCT and OCTa in neurodegenerative diseases. Results. Various studies have proven significant correlation between OCT measurements and neurodegenerative diseases. This increasingly developing correlation may help in the diagnosis and clinical treatment of these illnesses. However, there is a need for further studies and research to be conducted as non-specificity of OCT findings across the diseases remain a significant factor to be considered before mainstream usage. Conclusions. OCT usage has proved to be a field which deserves more gravity towards it. The anatomical origin as well as similarity of the eye and brain in function may help us understand and diagnose these diseases better in the foreseeable future.